2019
DOI: 10.2196/10813
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and Implementation of a Mobile Phone–Based Remote Symptom Monitoring System for People With Cancer in Europe

Abstract: Background There has been an international shift in health care, which has seen an increasing focus and development of technological and personalized at-home interventions that aim to improve health outcomes and patient-clinician communication. However, there is a notable lack of empirical evidence describing the preparatory steps of adapting and implementing technology of this kind across multiple countries and clinical settings. Objective This study aimed to describe … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 47 publications
1
56
0
1
Order By: Relevance
“…High compliance in all countries and all cancer types - Technical issues with the Web-based platform. Resolved with additional training of physicians - Modifications in ASyMS: longer time frame to provide feedback; changes in symptom algorithm - ASyMS not feasible in 2 centers due to organizational issues: lack of staff and technology connectivity Furlong [ 31 ] RCT in progress 1108 Breast, colorectal, hematologic receiving first-line CT Maguire [ 32 ] Automated voice response (AVR) system Yes Phone-based Symptom management toolkit, completed a baseline interview. Symptoms questionnaires about: fatigue, pain, insomnia, poor appetite, constipation, nausea/vomiting, anxiety, cough, depression, diarrhea, mouth sores, shortness of breath, peripheral neuropathy, difficulty remembering, and weakness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High compliance in all countries and all cancer types - Technical issues with the Web-based platform. Resolved with additional training of physicians - Modifications in ASyMS: longer time frame to provide feedback; changes in symptom algorithm - ASyMS not feasible in 2 centers due to organizational issues: lack of staff and technology connectivity Furlong [ 31 ] RCT in progress 1108 Breast, colorectal, hematologic receiving first-line CT Maguire [ 32 ] Automated voice response (AVR) system Yes Phone-based Symptom management toolkit, completed a baseline interview. Symptoms questionnaires about: fatigue, pain, insomnia, poor appetite, constipation, nausea/vomiting, anxiety, cough, depression, diarrhea, mouth sores, shortness of breath, peripheral neuropathy, difficulty remembering, and weakness.…”
Section: Resultsmentioning
confidence: 99%
“…- Fewer studies have assessed the feasibility of digital solutions from the HCP perspective. The most important reasons for adoption reported by HCPs were the usability and usefulness of the tool [26,38,52,58], and the most commonly reported barrier was problems with technology or connectivity [31,75].…”
Section: Drivers and Barriers To Usagementioning
confidence: 99%
“…Evidence supports eHealth's potential to fuel innovation. In particular, studies testing eHealth applications embedded within integrated care models (ICMs) for chronically ill persons have shown clear links to improved clinical, behavioral, and economic outcomes (Aapro et al, 2020;Barello et al, 2016;Elbert et al, 2014;Kuijpers, Groen, Aaronson, & van Harten, 2013;Michaud, Zhou, McCarthy, Siahpush, & Su, 2018;Warrington et al, 2019).…”
mentioning
confidence: 99%
“…However, despite increasing empirical evidence supporting eHealth integration into care delivery, sustained implementations of eHealth solutions in routine clinical practice are rare: uptake is often insufficient, adoption rates low, and sustained use rates lower still (Bates & Wright, 2009; Elbert et al, 2014; Furlong et al, 2019; Widmer et al, 2015). Studies testing ready‐made eHealth tools commonly report serious adoption and sustainment problems, with 44% to 67% of patients prematurely discontinuing use (Jeffs et al, 2016; Simblett et al, 2018; Thies, Anderson, & Cramer, 2017).…”
mentioning
confidence: 99%
“…In total, 17 web-based e-SRS were reported in 22 studies (22/33, 66%) [27][28][29][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49], including 2 studies that integrated web-based platforms with patient portals and electronic health records (EHRs) [41,47]. A total of 9 studies presented 7 mobile app-based e-SRS (9/33, 27%) [30,[50][51][52][53][54][55][56][57], 1 study reported an interactive voice response system [58], and 1 study used only text messaging for symptom reporting [59]. The most commonly adopted symptom reporting instruments or questionnaires in home-based e-SRS were the National Cancer Institute-Common Terminology Criteria for Adverse Events or patient-reported outcome version of Common Terminology Criteria for Adverse Events (6/33, 19%) [27,28,30,38,46,48] [28,31,45,…”
Section: Summary Of Study Characteristicsmentioning
confidence: 99%